Ulasan dan rating pelanggan online sebagai pendorong utama niat pembelian: Peran mediasi kepercayaan - Eliya Azis; Arthur Sitaniapessy; Weni Novandari (Jurnal Manajemen Maranatha, 2025)
Findings related to the relationship between the effect of online customer reviews and ratings, with trust as a mediating factor toward purchase intent are still different or inconsistent. Meanwhile, digital businesses utilize online customer reviews and ratings as factors in the process of determination decision buying consumer and marketing strategies. The goal of this research is to test the influence of online customer reviews and ratings mediated by trust on purchase intentions in smartphone consumers at the official store Shopee Indonesia. With a quantitive approach, the data involved 209 respondents who had shopped at Shopee. The non-probability sampling method and purposive sampling technique were applied to obtain the sample, with PLS-SEM utilized for data analysis in this study. The exploration found that there had appeared to be no significant direct effect online customer reviews toward purchase intent, in contrast to previous studies on positive and significant direct effects of such relationships. This research discovered that there was an indirect impact of online customer reviews toward purchase intent that was fully mediated by trust, and there was an indirect influence on online customer ratings toward purchase intent that was partially mediated by trust. This research emphasizes that reviews and ratings given by customers online are social influences that shape consumer perception of trustworthiness of products and vendors in online marketplaces, as stated by Social Influence Theory. Therefore, to develop consumer trust, digital commerce businesses are required to continuously observe and respond to customer reviews and ratings. Meanwhile, to maintain quality information, digital commerce platforms have responsibility to provide features that make the process more accessible to customers to offer truthful and relevant feedback, as well as filter out uncredible reviews.